Speaking my mind : expression and self-knowledge - Bar-On, Dorit, 1955- (Clarendon Press ; Oxford University Press, 2004)
The author develops and defends an original view of avowals and self-knowledge which offers systematic answers to many persistent questions concerning our ability to know our own minds.